2020
DOI: 10.3390/app10207126
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of iBeacon Deployment for Location-Based Services in Physical Learning Spaces

Abstract: Bluetooth Low Energy (BLE) is a wireless network technology used for transmitting data over short distances. BLE maintains a data transmission range comparable to the regular Bluetooth transmission, but consumes less energy and cost. iBeacon technology refers to BLE mobile devices, which allow mobile applications to receive signals from iBeacons in both indoor and outdoor environments. It is commonly used nowadays for positioning, location services, navigation and marketing, for the sustainable development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, research has found that the greatest signal attenuation and variation was caused by pedestrian traffic blocking the line of sight between transmitter and receiver, which is something to consider when placing the Bluetooth beacons for the treasure hunt (Kwok et al, 2020). High temperature and strong winds also caused minor discrepancies to the signals, whereas trees and nearby vehicle traffic did not have any negative effects on the signals (Kwok et al, 2020). This highlights the importance of the placement of the BLE beacons for the treasure hunt locations.…”
Section: System Limitationsmentioning
confidence: 99%
“…However, research has found that the greatest signal attenuation and variation was caused by pedestrian traffic blocking the line of sight between transmitter and receiver, which is something to consider when placing the Bluetooth beacons for the treasure hunt (Kwok et al, 2020). High temperature and strong winds also caused minor discrepancies to the signals, whereas trees and nearby vehicle traffic did not have any negative effects on the signals (Kwok et al, 2020). This highlights the importance of the placement of the BLE beacons for the treasure hunt locations.…”
Section: System Limitationsmentioning
confidence: 99%
“…When the signal abnormality detector determines that there is AP loss, the proposed algorithm only considers the signal space distortion of trusted APs, while it does not consider the signal space distortion of untrusted APs, which greatly reduce the matching error caused by signal loss. erefore, when the signal abnormality detector determines that there is AP loss, the corrected Euclidean distance can be calculated according to formula (7), while when the signal abnormality detector determines that there is no AP loss, Euclidean distance is still calculated according to formula (8). Suppose that the new Euclidean distance is defined as D, and the fingerprint matching criterion can be expressed as formula ( 9):…”
Section: Signal Distance Correctormentioning
confidence: 99%
“…At present, varieties of technologies are continuously implemented in indoor positioning fields, including Ultrasonic Positioning [4,5], Geomagnetic Positioning [6], Bluetooth Positioning [7,8], UWB Positioning [9], and Wi-Fi Positioning [10,11]. Among these technologies, Wi-Fi Positioning is the most prominent, as it has advantages in terms of vast communication range, low cost, convenient deployment, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Beacon can be found in many camera lenses [ 3 ], LED lighting [ 4 ], PoS devices [ 5 ], and digital billboards [ 6 ]; meanwhile, the popularity of smartphones, network devices, and location-based applications [ 7 ], as well as the low accuracy of GPS systems in indoor environments, have contributed to the expansion of the global indoor positioning market. The potential applications include locating children [ 8 ], the elderly [ 9 ], or pets [ 10 ] who have been lost; shopping mall navigation [ 11 ]; entry, exit, and crowd flow management at large venues (e.g., supermarkets or department stores) [ 12 ]; and vehicle management and identification [ 13 ]. The higher expansion of iBeacon and BLE Beacon applications often leads to higher risks associated with these applications.…”
Section: Introductionmentioning
confidence: 99%